Knowledge, attitude and practice about menstruation and menstrual hygiene among adolescent school girls of rural field practice area of tertiary care hospital, Nandyal, Andhra Pradesh: a cross-sectional study - Reddy, Kamuni Madhuri; Pasha, M. A. M.; Fatima, Afsar (International Journal Of Community Medicine And Public Health, 2024)
Background: As the reproduction starts from the puberty and in which most of the girls will be not aware of menstruation and they will lack the knowledge as most of the girls will be in school age group. This study is done to understand their knowledge, attitude and practice on menstruation and menstrual hygiene in school going girls. Methods: A school based cross sectional study was conducted after getting ethics committee clearance during August-September 2023 (2 months) in RHTC field area of Santhiram medical college, Nandyal among high school girls of 8th, 9th and 10th classes by simple random sampling method with sample size 230, study tool was pre-designed, pre-tested, semi structured questionnaire by interview method collected data and analysed by SPSS 25 version. Results: In this study out of 230 participants about 43% were under the age group 13 years, 57.8% were have knowledge on menstruation and 60% were not aware of origin of blood and 76.1% are attending school during the menses, 31% of girls Still feels embarrassing buying pads, 40% don’t attend to perform house activities and sitting at the corner. Only 51.7% are using dustbins for disposal. Conclusions: This study results shows that girls have a poor knowledge, attitudes and practices regarding menstruation and menstrual hygiene. There is a gap between knowledge and menstrual hygiene and usage of proper sanitation, school administration and health facilities should conduct awareness programmes on menstrual hygiene.